Caso e formazione. Note di pedagogia leopardiana - Zedda, Michele (Studi sulla Formazione/Open Journal of Education, 2023)
Leopardi has examined the influence of the case on human life. Fortune and circumstances have a great influence on everything: health, genius, courses of life, study and education. Therefore, it’s not easy to foresee results of a formative programme. This Leopardi’s position completes his theory of custom and balances its theoretic importance.